2015
DOI: 10.1007/s00392-015-0834-3
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of peripheral arterial disease in patients with obstructive sleep apnoea

Abstract: OSA is associated with a high prevalence of PAD. This implies substantial diseasés under-recognition and a presumable atherogenic role of OSA in the pathogenesis of PAD. However, vasoprotective impact of OSA treatment remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…Indeed, ankle-brachial PWV assesses arterial stiffness over the aortic segment and also in the lower limbs. The brachial-ankle PWV or the Cardio-Ankle Vascular Index (CAVI), another non-standard measure of arterial stiffness, should not be used in patients with peripheral arterial disease (PAD), a very highly prevalent condition in patients with OSA 32. Alberto et al carefully excluded patients with PAD in their study and only observed a non-significant trend between CAVI and nocturnal intermittent hypoxia 33…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ankle-brachial PWV assesses arterial stiffness over the aortic segment and also in the lower limbs. The brachial-ankle PWV or the Cardio-Ankle Vascular Index (CAVI), another non-standard measure of arterial stiffness, should not be used in patients with peripheral arterial disease (PAD), a very highly prevalent condition in patients with OSA 32. Alberto et al carefully excluded patients with PAD in their study and only observed a non-significant trend between CAVI and nocturnal intermittent hypoxia 33…”
Section: Discussionmentioning
confidence: 99%
“…The presence of altered concentrations, cell sources, and intrinsic properties of circulating microvesicles have been previously noted by several investigators in the context of OSA, whereby the ability of these microvesicles to induce coagulation, angiogenesis, and cell adhesion was noted, and globally believed to reflect a proatherogenic state. 9,[42][43][44][45] The enhanced pro-atherogenic state of OSA is further exemplified by not only the high cardiovascular morbidity burden of this condition, 46 but also by the elevated prevalence of peripheral vascular disease in OSA patients, 47 and multiple investigators have explored the vascular consequences of OSA in different settings. [48][49][50] Our study relied on healthy young adults subjected to a relatively brief IH exposure, such that we can only infer that more chronic exposures to IH in the context of OSA may further exacerbate the pathological changes induced by the disease, and hypothesize that the exosome-related activity on the endothelium will contribute to such processes, as illustrated by the current in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a Taiwanese nationwide case-control study using population-based claims data, cases with sleep apnea diagnosed by clinical symptoms and/or AHI≥5 events/hr were 30% more likely to have been diagnosed with PAD than controls [20]. Additionally, in small clinical samples (N≤100), prevalent PAD among patients with suspected sleep apnea was high [21], as was prevalent sleep apnea among PAD patients needing surgical revascularization[22]. Sleep apnea defined by AHI≥20 was also associated with long-term morbidity and mortality after surgical revascularization in 84 PAD patients[23].…”
Section: Discussionmentioning
confidence: 99%